Collagen Structure Deterioration in the Skin of Patients with Pelvic Organ Prolapse Determined by Atomic Force Microscopy. (5th March 2015) - Kotova, Svetlana L.; Timashev, Peter S.; Guller, Anna E.; Shekhter, Anatoly B.; Misurkin, Pavel I.; Bagratashvili, Victor N.; Solovieva, Anna B.
Abstract: We used atomic force microscopy (AFM) to diagnose pathological changes in the extracellular matrix (ECM) of skin connective tissue in patients with pelvic organ prolapse (POP). POP is a common condition affecting women that considerably decreases the patients' quality of life. Deviations from normal morphology of the skin ECM from patients with POP occur including packing and arrangement of individual collagen fibers and arrangement of collagen fibrils. The nanoindentation study revealed significant deterioration of the mechanical properties of collagen fibril bundles in the skin of POP patients as compared with the skin of healthy subjects. Changes in the skin ECM appeared to correlate well with changes in the ECM of the pelvic ligament tissue associated with POP. AFM data on the ECM structure of normal and pathologically altered connective tissue were in agreement with results of the standard histological study on the same clinical specimens. Thus, AFM and related techniques may serve as independent or complementary diagnostic tools for tracking POP-related pathological changes of connective tissue.